2021
DOI: 10.1101/2021.01.13.21249645
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic markers distinguish COVID-19 from other intensive care patients and show potential to stratify for disease risk

Abstract: Coronavirus disease 2019 (COVID-19) is a viral infection affecting multiple organ systems of great significance for metabolic processes. Thus. there is increasing interest in metabolic and lipoprotein signatures of the disease and early analyses have demonstrated metabolic pattern typical for atherosclerotic and hepatic damage in COVID-19 patients. However, it remains unclear whether these are specific for COVID-19 or a general marker of critical illness. To answer this question, we have analyzed 276 serum sam… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
3
8
0
Order By: Relevance
“…Immune-activated and oxygen-deprived cells show metabolic signatures associated with the increase in glycolytic pathways and glutamine metabolism that feed energetic and biosynthetic processes [ 44 47 ]. In this vein and in line with other studies [ 48 53 ] we observed decreased serum glutamine and high glutamic acid levels in patients with severe COVID-19. Further, applying pathway enrichment analysis, we detected statistical significance and enrichment ratio of glutamine/glutamate metabolism.…”
Section: Discussionsupporting
confidence: 94%
“…Immune-activated and oxygen-deprived cells show metabolic signatures associated with the increase in glycolytic pathways and glutamine metabolism that feed energetic and biosynthetic processes [ 44 47 ]. In this vein and in line with other studies [ 48 53 ] we observed decreased serum glutamine and high glutamic acid levels in patients with severe COVID-19. Further, applying pathway enrichment analysis, we detected statistical significance and enrichment ratio of glutamine/glutamate metabolism.…”
Section: Discussionsupporting
confidence: 94%
“…The metabolic profile that we observe for COVID-19 compared with controls is largely in agreement with those previously published for cohorts in Spain and Australia (Bruzzone et al, 2020;Kimhofer et al, 2020). In general, several markers dysregulated in COVID-19 were reported earlier by others and in a preliminary study of ourselves (Schmelter et al, 2021), including increased levels of phenylalanine, glucose, and formic acid, as well as reduced levels of glutamine, histidine, and lactic acid. In opposite to the Spanish cohort, we do not see changes in ketone bodies, but the patients in our COVID-19 cohort did not receive glucose infusions, which is a likely cause for this difference, also reflected in lower glucose levels in our results.…”
Section: Discussionsupporting
confidence: 92%
“…Lipoprotein analyses showed increased very-low-density lipoprotein (VLDL) and intermediate-density lipoprotein (IDL) (sub)-fractions and decreased high-density (HDL) levels in both studies ( Bruzzone et al, 2020 ; Kimhofer et al, 2020 ). In a preliminary report, we have previously reported a very similar signature derived from nuclear magnetic resonance (NMR) metabolomics ( Schmelter et al, 2021 ) characterized by increased levels of glutamic acid, phenylalanine, and glucose, which is consistent with the findings of the two other studies ( Bruzzone et al, 2020 ; Kimhofer et al, 2020 ). These results seem to underline systemic defects associated with COVID-19 and demonstrate the suitability of metabolomics for the detection and potentially stratification of COVID-19 patients.…”
Section: Introductionsupporting
confidence: 86%
“…DIRE NMR experiments when applied to the plasma of SARS-CoV-2 positive and negative and control patients revealed a strong diagnostic pattern involving lipoprotein-bound phospholipid and glycoprotein signals . Additionally, we and others have shown that NMR-generated lipoprotein signals are profoundly altered in SARS-CoV-2 infection and that some of these lipoproteins give further information on cardiovascular disease risk factors that can then be statistically linked to novel disease biomarkers.…”
Section: Introductionmentioning
confidence: 63%